(untitled) (Texas Journal of Multidisciplinary Studies, 2025)
This article describes the processes of reforming the trade union system and the essence of effective solutions to the obstacles that are a source of it. Issues of the formation of the principles of democracy and transparency in the activities of trade unions are revealed.